Potensi Pemanfaatan Nigella sativa L. sebagaiImunomodulator dan Antiinflamasi - Sulistiawati, Farida; Radji, Maksum (UI Scholars Hub, 2014)
Nigella sativa L. has long been used as an herbal medicine in some countries, particularly in the Middle East and in other Asian countries, including in Indonesia. One component is a protein compound extracted from black cumin oil residues, known to have efficacy to enhance the immune system and as an anti-inflammatory. As the compound will be degraded when administered orally, the research on its delivery systems, is interesting to be developed. This article will review about the prospects of their utilization and strategy formulation that preparation can be delivered orally.